Efficacy of Liposomal Bupivacaine Compared with Multimodal Periarticular Injections for Postoperative Pain Control following Total Knee Arthroplasty - Britten, Tyler; Hughes, Jonathan D.; Munoz Maldonado, Yolanda; Hitt, Kirby D. (The Journal of Knee Surgery, 2019)
Single-dose long-acting periarticular anesthetics have been shown to be an effective method of postoperative analgesia in total knee arthroplasty (TKA). This study retrospectively compares the efficacy of multimodal periarticular injection consisting of a combination of ropivacaine, duramorph, epinephrine, and toradol (HC) with liposomal bupivacaine (LB) periarticular injection in TKA. This study was a retrospective matched comparative chart review of two cohorts of patients who underwent TKA within a single health care system and cared for by one provider. We compared 22 patients who were treated with LB intraoperatively (LBG) with 41 matched controls who were treated with HC periarticular injection (HCG). These cases were retrospectively reviewed at 0 to 6, 6 to 12, 12 to 24, 24 to 48, and 48 to 72 hours. We reviewed pain scores and opioid use per the preceding time period, total opioid use, length of stay (LOS), and wound complications between the two groups. The two groups showed no statistical difference in total opioids used. In both the 6- to 12-hour and 12- to 24-hour intervals, the LBG required significantly more opioids than the HCG, with p-values of 0.0039 and 0.0061, respectively. Pain scores were not significantly different for any time period. We found no difference in LOS. The LBG tended to have lower doses of antiemetics than the HCG. No significant difference was found in postoperative pain scores and total opioid use between LB and multimodal periarticular intraoperative injections in TKA. Our data demonstrated decreased opioid consumption in the HC group compared with the LB group in both the 6- to 12-hour and 12- to 24-hour time intervals postoperatively. At our institution, LB costs US$314.99, whereas HC costs US$95.
Keywords: liposomal bupivacaine; periarticular injection; knee arthroplasty